Knowledge, Attitudes and Perception in Regard to COVID-19 Pandemic in Nigerian Military Population - Ogbole, A. J.; Bisji, J. S.; Umar, S. J.; Jallo, I. M.; Ezeh , S. O.; James, A. L. (Advances in Social Sciences Research Journal, 2020)
The study assessed the knowledge, attitudes and perception of Nigerian Military population towards the coronavirus outbreak. A web-based cross-sectional survey was used to collect from 216 data from military officers from the Nigerian Army, Nigerian Air Force and the Nigerian Navy. Majority of the study sample were males, 88.4% (n = 191) and more than half the respondents were between 21 to 30 years old (50.5%). Also, 82.4% of the sample were graduates and 54.2% married. 82.9% were from Nigerian Army and 57.9% were commissioned officers with 6-10 years’ work experience 49.5 (n=107). Results show that there was no significant correlation between demographic factors of gender, age, military type, religion, education and marital status and knowledge of COVID-19 (p>.05). Results further show that there was no significant correlation between demographic factors and perception of COVID-19 (p>.05), meaning there was no significant difference in perception of COVID-19 based on demographic factors. Finally, the results showed that there was no significant correlation between demographic factors and attitude to COVID-19 (p>.05). Irrespective of gender or age for example, knowledge, attitude, and perception of COVID-19 was good among the military population. Despites high level of awareness among the study population, it was recommended that the military authorities in Nigeria further strengthen their health systems, as well as the knowledge of infectious diseases and pandemics which will help them to assist the government and in educating the general populace through their military-civilian interface.